Studies on Populations Exposed to Polychlorinated Biphenyls - Kreiss, Kathleen (Environmental health perspectives, 1985)
Mean serum levels of polychlorinated biphenyls (PCBs) in U.S. population groups without occupational exposure to PCBs are usually between 4 and 8 ng/mL, with 95% of individuals having serum PCB measurements of less than 20. Subpopulations consuming fish taken from contaminated waters, such as Lake Michigan and near Triana, AL, have mean serum PCB levels several times those found in other general population groups and ranges that extend into concentrations found in industrial populations involved in capacitor manufacture. Two studies of general populations and several studies of industrial workers have demonstrated associations of PCBs with various serum lipids and liver enzyme levels. Six groups of investigators have found associations between PCB or chlorinated pesticide levels and blood pressure. Research efforts are needed in clarifying determinants of serum-adipose partition ratios; the utility of urinary porphyrins as a measure of subclinical hepatic effects; human metabolites and excretion of chlorinated hydrocarbons; and the relation, if any, between blood pressure and organochlorine compounds when controlled for confounding variables. Established cohorts, such as those in Triana, Lake Michigan sportsfishers, the Michigan PBB cohort, residents of farms with PCB-lined silos, and occupational groups, could all be studied further with attention to these research questions.